PENGEMBANGAN MOBILE EDUKASI MATEMATIKA BERBASIS KEARIFAN LOKAL JAWA SEBAGAI MEDIA PEMBELAJARAN MATEMATIKA ANAK SEKOLAH DASAR - Setiyono, Hendri; Buchori, Ahmad; Indriati Wardani, Theodora (Universitas PGRI Semarang, 2023)
Media education is an activity of the learning process and training to change attitudes in maturation by the group. So it is not uncommon for students to use technological advances just to play not to learn. With this mobile mathematics education with Javanese local wisdom, it is hoped that it can help students understand the material easily and increase student interest in learning. The purpose of this research is to find out valid, practical, and effective as a medium of learning for children in learning. The method used in this study is the ADDIE model method, which stages include: analysis, design, development, implementation and evaluation stages. The results of this study indicate that the effectiveness assessment using the Statistical Test results in a significance value of 0.541 so that it is included in the